Mesoscopic superconductivty in application - Barba-Ortega, J.; Bautista-Ruiz, J.; Sardella, E. [UNESP]; IOP (Iop Publishing Ltd, 2018)
The Ginzburg-Landau theory, applied to superconducting materials is based on thermo-magneto-electro-dynamic concepts as phase transitions that enrich the class on this subject. Thus, in this contribution we expose the Ginzburg-Landau time-dependent equations, show the mathematical form for two nano-scale superconducting systems, one bi-dimensional homogeneous al sample with applied external current at zero magnetic field, and one three-dimensional cube in presence of a tilted magnetic fiel at zero applied current. This analysis shows the applicability of the three and two-dimensional model to superconductors. The conveniently Ginzburg-Landau theory show that the magnetic response behavior of the sample is very useful for applications in fluxtronica, SQUIDS design, magnetic resonance, among others.